Gridlock : Labor, Migration, and Human Trafficking in Dubai. - Mahdavi, Pardis (Stanford University Press, 2011)
The images of human trafficking are all too often reduced to media tales of helpless young women taken by heavily accented, dark-skinned captors--but the reality is a far cry from this stereotype. In the Middle East, Dubai has been accused of being a hotbed of trafficking. Pardis Mahdavi, however, draws a more complicated and more personal picture of this city filled with migrants. Not all migrant workers are trapped, tricked, and abused. Like anyone else, they make choices to better their lives, though the risk of ending up in bad situations is high. Legislators hoping to combat human traffick.